Population Of Bacteria In Soil Dystrudepts Under Oil Palm In The Application Of Organic Mulch And Earthworm - Juliarni Juliarni; Wawan Wawan; Delita Zul (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2021)
Research on the effect of organic mulch and earthworms under oil palm plantation on the total population bacteria is still scarce. The study aims to analyze the effect of organich mulch, earthworm desity, and the interaction between organich mulch and earthworm density on the total population bacteria. The research was carried out in May – August 2019. This research was a 3 x 4 factorial experiment which was placed according to a Split Plot Design with the basic design of Randomized Block Design, each treatment was repeated 3 times. Organic mulch as the main plot are 3 type, namely: M1 (M. bracteata), M2 (oil palm empty fruit brunches/ OPEFB) and M3 (oil palm midrib). The density of earthworms as subplots consists of 4 levels, namely: C0 (0 worms/m2), C1 (35 worms/m2), C2 (50 worms/m2) and C3 (65 worms/m2). The data were analyzed using analysis of variance. If the treatment is significantly different, the treatment was tested by Duncan’s at 5% significance level. The results showed that oil palm midrib organic mulch can increase the total population of fungi and bacteria compared to M. bracteata and OPFEB. The earthworms density 50 and 65 worms/m2 can increase the total bacterial population compared to other earthworm densities. The combination of oil palm midrib with earthworms density 50 and 65 worms/m2 can increase the total population of bacteria